Essentials for a health service : a memorandum presented by the Communist Party to the Minister of Health. (London : Communist Party, 1946)
1946 1946 1940s 12 pages ESSENTIALS for a HEALTH SERVICE A Memorandum Presented by THE COMMUNIST PARTY to the MINISTER OF HEALTH Threepence 15X/2/103/357